Learning Strategies in Language Acquisition for Early Childhood Education - Yuli Ani Setyo Dewi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Early childhood education is an age that contains a golden period for the physical and mental development of children. At this time the child is very sensitive to all the influences given by his environment. This study aims to know the strategy used by early childhood education in language acquisition. It is described using the perspectives of several specialists. So, this study is anticipated to give thorough information regarding Language Acquisition Learning Techniques for Early Childhood Education by employing a qualitative method. The result shows that the idea places a strong emphasis on pronunciation, memory, and fundamental communication. ‎To achieve language acquisition for early childhood, there are a variety of learning strategies. Such as Total Physical Response (TPR), Using Song to Teach English, and Using Games to Teach English. With the right strategy, educators can maximize children's early age to master foreign languages.